Energy-based nonlinear damage creep model considering the influence of the concrete creep rate - Wang, Lu (Frontiers in Materials, 2025)
In order to study the influence of confining pressure on the deformation of concrete, triaxial compression and creep tests under different confining pressures are carried out using a combination of laboratory tests and theoretical analysis. Based on the whole creep process curve of concrete and the energy conservation theorem, viscoplastic and accelerated creep models are established by introducing loading rate equations at different stages. Taking time and stress as the triggering conditions of the creep model, the model parameters are identified by fitting the test curve, and a nonlinear creep damage model is established, which can better reflect the creep development characteristics of concrete. The results showed that the fitting curves closely matched the test results. The newly established damage creep model can better describe the deformation characteristics of the creep failure stage under different confining pressures and stress levels. It can effectively describe the nonlinear creep development trend of concrete during the accelerated creep stage. In general, the creep model has a high degree of accuracy in capturing the damage description of concrete.